Engaging Indigenous Peoples and Local Communities in Environmental Management Could Alleviate Scale Mismatches in Social–Ecological Systems. (8th July 2020) - Herse, Mark R; Lyver, Phil O'B; Scott, Nigel; McIntosh, Angus R; Coats, Simon C; Gormley, Andrew M; Tylianakis, Jason M
Abstract: Scale mismatches in social–ecological systems constrain conservation by obscuring signals of environmental change, which could otherwise feed back to inform adaptive responses and solutions. We argue that engaging indigenous peoples and local communities (IPLC) in place-based environmental management could generate the fine-resolution information and workforce needed to alleviate scale mismatches. We illustrate our argument using a case study initiated by Māori in Aotearoa/New Zealand and demonstrate that the current broad scales of hunting regulation and assessment in black swan (kakī anau, Cygnus atratus) management could obscure local ecological drivers of populations. Many IPLC can facilitate adaptive place-based management by continually monitoring ecological feedbacks (e.g., population numbers, habitat conditions) at fine resolutions through customary resource use and observations. However, disregard for IPLC rights, scepticism of traditional ecological knowledge, restricted opportunity to connect with resources, compartmentalization of resource management, and insufficient funding limit IPLC engagement and must be overcome to alleviate scale mismatches.